Factors Affecting Utilization of Evaluations in Selected Non-Profit Organizations in Kenya - Letoya, paul Saitoti; Omwenga, Dr. Jane (International Journal of Entrepreneurship and Project Management, 2016)
Purpose: The aim of this researchwasto establish what factors affect utilization of evaluationrecommendations among Non-government organizations. Methodology: The study adopted a descriptive,cross-sectional research designwith a quantitativeapproach.A sample size of 48 CRS (63%) and partner organizations' (37%) staff was calculated based on Slovin's sampling formula at a confidence level of 95% from a sample frame of 60. Multi-stage sampling technique was used with probability proportional to size (PPS) for the first stage,that distributedthe sample between CRS and partner,and systematic random sampling for the second stage that selected individual respondents.An online semi-structured questionnaire was used to collect data before the data was exported onto Statistical Package for Social Sciences software where both descriptive and inferential statistical analysis was done.Use of technology was informed by the limitation of physical availability of respondents due to them being stationed in remote areas as well as frequent work travel for those based in Nairobi.Descriptive analysis providedcharacteristicsof respondents and responses while Inferential statistics was used to identify relationships among independent variables and between independent variables and dependent variables Results: Findings from the study showed that there was a negatively significant correlation between knowledge and use of evaluation.Evaluation policy and attitude were found to be significantly and positivelycorrelated with use of evaluation while disseminationpracticewas not correlated with use of evaluations. Unique contribution to theory, practice, and policy: This concluded that knowledge,attitude, and policy affected utilization of evaluations but dissemination practice did not.The study recommended strengthening and enforcement of evaluation policy,review of the content and facilitation of dissemination forums as well continued sensitization on theimportance and how to implement evaluation recommendations.